Сравнительная характеристика особенностей репродукции коренных этносов Сибири - Ульянова, М.В.; Лавряшина, М.Б.; Дружинин, В.Г. (Фактори експериментальної еволюції організмів, 2014)
Aims. Identify peculiarities of reproduction in indigenous Siberian ethnic groups: Altai, Khakassia, Shor, Siberian Tatars and assess the impact factor of natural selection. Methods. According to demographic profiles were analyzed age and vital characteristics. Based on vital statistics parameters of natural selection were calculated by the method proposed by Crow. Results. Khakases and Siberian Tatar shown earlier age at menarche compared with Altais. Physiological reproductive period in all ethnic groups was 33–34 years old, the actual reproductive period – less than 1/3 of the physiological. The research showed a reduction in the level of prenatal and pre-reproductive losses, the average number of pregnancies and live births per generation in all ethnic groups. Conclusions. Indigenous peoples of Siberia differ from each other by peculiarity of reproductive health indicators and reproductive behavior. In all groups of indigenous peoples of Siberia revealed the presence of the demographic transition to narrowed level of natural reproduction. The values were calculated by Crow’s index (Itot) and it is shows a higher pressure of natural selection in populations of Shor and Siberian Tatars.